Anteromedializing Tibial Tubercle Osteotomy for Patellofemoral Instability: Occupational and Functional Outcomes in U.S. Military Service Members - Belmont, Philip J., Jr.; Fisher, Tuesday F.; Bader, Julia M.; Lanzi, Joseph T.; Owens, Brett D.; Waterman, Brian R. (The Journal of Knee Surgery, 2018)
This article sought to determine rates for return to work, pain relief, and recurrent patellofemoral instability for military service members undergoing tibial tubercle osteotomy (TTO) for persistent lateral patellar subluxation or dislocation. Patient demographic and surgical variables were isolated from the medical records of active duty service members with at least 2 years of postoperative follow-up, and correlated with return to work, pain improvement, recurrent patellofemoral instability, and perioperative complications. There were 51 service members (58 primary TTOs) with an average follow-up of 3.3 (range, 2.0–6.7) years. Service members had an average of 2.8 (1–12) instability events preoperatively. At a minimum of 2 years postoperatively, 41 (80%) military service members returned to full active duty service. Among the 58 TTOs, there was a 46% improvement in the patient-reported visual analog score from 4.1 to 2.2 (p < 0001). The postoperative recurrent instability rates were patellar dislocation (5.1%) and patellar subluxation (15.5%). Concomitant proximal realignment was performed in 48% of cases, which did not affect return to service, postoperative patellar instability events, or pain improvement (p > 0.05). The overall complication rate was 10%. Postoperative tibial fractures occurred in 6.9% of TTOs. At short- to mid-term follow-up, 80% of service members undergoing TTO for patellofemoral instability returned to military duty with significant improvement in pain scores and a moderate perioperative complication and postoperative instability rate. This study is a level IV therapeutic case series.
Keywords: tibial tubercle osteotomy; anteromedialization; patellar instability; military; functional outcome